Varying‐coefficient semiparametric model averaging prediction. Issue 4 (18th May 2018) - Li, Jialiang; Xia, Xiaochao; Wong, Weng Kee; Nott, David
Summary: Forecasting and predictive inference are fundamental data analysis tasks. Most studies employ parametric approaches making strong assumptions about the data generating process. On the other hand, while nonparametric models are applied, it is sometimes found in situations involving low signal to noise ratios or large numbers of covariates that their performance is unsatisfactory. We propose a new varying‐coefficient semiparametric model averaging prediction (VC‐SMAP) approach to analyze large data sets with abundant covariates. Performance of the procedure is investigated with numerical examples. Even though model averaging has been extensively investigated in the literature, very few authors have considered averaging a set of semiparametric models. Our proposed model averaging approach provides more flexibility than parametric methods, while being more stable and easily implemented than fully multivariate nonparametric varying‐coefficient models. We supply numerical evidence to justify the effectiveness of our methodology.